BRAF‐V600E immunohistochemistry in a large series of glial and glial–neuronal tumors. Issue 3 (10th February 2017) - Breton, Quentin; Plouhinec, Hélène; Prunier‐Mirebeau, Delphine; Boisselier, Blandine; Michalak, Sophie; Menei, Philippe; Rousseau, Audrey
Abstract: Introduction: Some glial–neuronal tumors (GNT) (pleomorphic xantho‐astrocytoma [PXA], ganglioglioma [GG]) display BRAF‐V600E mutation, which represents a diagnostic clue to these entities. Targeted therapies against BRAF‐V600 protein have shown promising results in GNT. The aim of this study was to assess the utility of BRAF‐V600E immunohistochemistry (IHC, clone VE1) in daily practice in a series of 140 glial, and GNT compared to molecular biology (MB) techniques. Methods: We performed BRAF‐V600E IHC on all 140 cases. We used Sanger sequencing and allele‐specific quantitative PCR (ASQ‐PCR) to detect BRAF‐V600E mutation when sufficient amount of materiel was available. Results: BRAF‐V600E immunostaining was detected in 29.5% of cases (41/140 cases; 61.5% GG/GC/AGG (32/52), 33% PXA, 6.6% pilocytic astrocytomas). In 47 cases, MB could be performed: Sanger sequencing and ASQ‐PCR in 34 cases, ASQ‐PCR only in 11 cases, and Sanger sequencing only in two cases. In initial tumors, Sanger sequencing identified BRAF‐V600E mutation in 19.5% tumors (seven of 36 tested cases). ASQ‐PCR showed mutation in 48.5% tumors (17/35 tested cases). In six cases (5 GG, one PXA), the results were discordant between IHC and MB; the five GG cases were immunopositive for BRAF‐V600E but wild type with both MB techniques. In another 7 GG, the percentage of mutated (ganglion) cells was low, and Sanger sequencing failed to detect the mutation, which was detected by IHC and ASQ‐PCR. Conclusions: In tumors with few mutated cells (e.g., GG), anti‐BRAF‐V600E IHC appears more sensitive than Sanger sequencing. The latter, although considered as the gold standard, is not to be used up‐front to detect BRAF mutation in GG. The combination of IHC and ASQ‐PCR appears more efficient to appraise the indication of targeted therapies in these glioneuronal tumors. Abstract : The aim of this study was to assess the utility of BRAF‐V600E immunohistochemistry (IHC, clone VE1) in daily practice in a series of 140 glial and glial–neuronal tumors compared to molecular biology (MB) techniques. This work shows that the combination of IHC and ASQ‐PCR appears more efficient to appraise the indication of targeted therapies in glioneuronal tumors.